Evaluation of the Antiviral Activity Against Infectious Pancreatic Necrosis Virus (Ipnv) of a Copper (I) Homoleptic Complex with a Coumarin as Ligand - Guerrero-Nunez, J; Guerrero-Nunez, J; Modak-Canobra, B; Mascayano-Collado, C; Valenzuela-Montenegro, B; Olguin-Gonzalez, A; Aldabaldetrecu-Urbieta, M; Aldabaldetrecu-Urbieta, M (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The aquatic infectious pancreatic necrosis virus (IPNV) causes a severe disease in farmed salmonid fish that generates great economic losses in the aquaculture industry. In the search for new tools to control the disease, in this paper we show the results obtained from the evaluation of the antiviral effect of [Cu(NN1)2](ClO4) Cu(I) complex, synthesized in our laboratory, where the NN1 ligand is a synthetic derivate of the natural compound coumarin. This complex demonstrated antiviral activity against IPNV at 5.0 and 15.0 µg/mL causing a decrease viral load 99.0% and 99.5%, respectively. The Molecular Docking studies carried out showed that the copper complex would interact with the VP2 protein, specifically in the S domain, altering the process of entry of the virus into the host cell. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.